Public knowledge and perceptions on family foster care: Contributes to it’s development - Negrão, Mariana (2019)
Family foster care is a child protection measure that gained representation throughout Europe in the last decades. Parallel, research underlines the better fit of family foster care to the developmental needs of at risk children and youth. However, in Portugal, this is still an underrepresented measure in the Child Protection System. Beyond many complex political, legal and financial aspects, the ability to promote family foster care, may be also dependent on the knowledge and perceptions that general public might have on the subject. This study analyses public (n=270) knowledge and perceptions about family foster care. Results show little knowledge about the out of home care system, but a favourable attitude towards family foster care and a high availability to become foster carer. Results are discussed taking into account its implications towards the promotion of a culture of family foster care and towards the strengthening of conditions that foster the development of the measure.